Pharmacological mechanisms underlying the efficacy of antibodies generated by a vaccine to treat oxycodone use disorder. (1st September 2021) - Raleigh, M.D.; King, S.J.; Baruffaldi, F.; Saykao, A.; Hamid, F.A.; Winston, S.; LeSage, M.G.; Pentel, P.R.; Pravetoni, M.
Abstract: Therapeutic vaccines offer a viable strategy to treat opioid use disorders (OUD) complementary to current pharmacotherapies. The candidate Oxy(Gly)4 -sKLH vaccine targeting oxycodone displayed pre-clinical proof of efficacy, selectivity and safety, and it is now undergoing clinical evaluation. To further support its implementation in the clinic, this study tested critical in vivo neuropsychopharmacological properties of the Oxy(Gly)4 -sKLH vaccine in rats. While repeated immunizations with Oxy(Gly)4 -sKLH were necessary to maintain the antibody response overtime, exposure to free oxycodone did not boost oxycodone-specific antibody levels in vaccinated rats, limiting concerns of immune-related side effects. Immunization with Oxy(Gly)4 -sKLH achieved sustained antibody titers over a period of five months following initial vaccination, supporting its potential for providing long-lasting protection. In vivo studies of selectivity showed that vaccination prevented oxycodone-induced but not methadone-induced antinociception, while still preserving the opioid antagonist naloxone's pharmacological effects. Vaccination did not interfere with fentanyl-induced antinociception or fentanyl distribution to the brain. These in vivo data confirm the previously reported in vitro selectivity profile of Oxy(Gly)4 -sKLH. Vaccination extended oxycodone's half-life up to 25 h compared to control. While vaccination reduced the reinforcing efficacy of oxycodone in an intravenous self-administration model, signs of toxicity were not observed. These rodent studies confirm that active immunization with Oxy(Gly)4 -sKLH induces highly specific and long-lasting antibodies which are effective in decreasing the reinforcing effects of oxycodone while preserving the efficacy of medications used to treat OUD and overdose. Highlights: Opioid use disorder is a worldwide problem and better treatments are needed. This study characterizes an oxycodone vaccine currently undergoing clinical testing. Exposure to oxycodone does not elicit antibody production in vaccinated animals. Vaccine blunts oxycodone, but not methadone, fentanyl, or naloxone effects. Vaccine alters oxycodone self-administration; no opioid-induced toxicity observed.